Dynamic analysis of laminated composite sandwich beam containing carbon nanotubes reinforced magnetorheological elastomer. (June 2021) - Selvaraj, Rajeshkumar; Ramamoorthy, Manoharan
In this study, dynamic analysis of three-layered sandwich beam with thin orthotropic skins and multiwall carbon nanotubes reinforced magnetorheological elastomer (MWCNT-MRE) core have been investigated. The laminates are made of glass fiber/epoxy composites with ply orientation of [0/90] s and are prepared using vacuum-assisted hand layup process. Experiments are performed to investigate the vibration characteristics of MWCNT-MRE and MRE sandwich structures by applying the various magnetic field intensities under different end conditions. Further, the laminated composite MWCNT-MRE and MRE sandwich beams are modeled using ABAQUS finite element software and validated through experimental results in terms of natural frequencies. Also, the present finite element model is validated with available literature in terms of natural frequencies. A very good agreement is observed between the results of the experimental method and those extracted from numerical simulation. Also, the influence of applied magnetic field levels, core thickness ratio, ply orientation, and various boundary conditions on the vibration behavior of laminated composite MWCNT-MRE and MRE sandwich beams are analyzed.